Annual Report 1989 - Venereal Disease and Yaws Division, Ministry of Health (Ministry of Health, Trinidad and Tobago, 1989)
The Venereal Disease and Yaws Division of the Ministry of Health of Trinidad and Tobago continued to take all possible efforts to reduce the high increase of the common Sexually Transmitted Diseases and to keep the others under control during the year 1989. The statistics given in this report relate to work done in the S.T.D. Clinics only. The figures for gonorrhoea showed a decline for the second consecutive year. Three thousand eight hundred and seven (3,807) cases were diagnosed and treated in 1989 as compared to four thousand three hundred and seventeen (4,317) in 1988 a decrease of five hundred and ten (510) cases or 11.8%.
Keywords: Sexually transmitted diseases